Burnout syndrome prevalence during internship in public and private hospitals: a survey study in Mexico. Issue 1 (1st January 2019) - Miranda-Ackerman, Roberto Carlos; Barbosa-Camacho, Francisco José; Sander-Möller, María José; Buenrostro-Jiménez, Arturo David; Mares-País, Roberto; Cortes-Flores, Ana Olivia; Morgan-Villela, Gilberto; Zuloaga-Fernández del Valle, Carlos José; Solano-Genesta, Manuel; Fuentes-Orozco, Clotilde; Cervantes-Cardona, Guillermo Alonso; Cervantes-Guevara, Gabino; et al.
ABSTRACT: Burnout syndrome is a psychological condition that commonly affects health professionals, medical students, and others in professions with long shifts. It is defined by a high amount of emotional exhaustion, depersonalization, and low personal job satisfaction. We aimed to determine the prevalence of burnout syndrome in medical interns and establish the relationships between this condition and the time and type of hospital at which students worked during their medical internship. This was a survey study in which we used the Maslach Burnout Inventory, applied to fifth-year medical students on an internship at private and public hospitals in Mexico. The participants were 96 women (54.5%) and 80 men (45.5%), with ages ranging from 21 to 34 years old. We found burnout syndrome in 20% of these medical students 22% of the women and 18.6% of the men in the sample. Second-semester interns suffered burnout at a rate of 29%, in contrast to 15% of first-semester students. Emotional exhaustion and depersonalization scores were higher in second-semester interns who worked in public hospitals. However, the prevalence did not differ between public and private hospitals. Our study reports a higher prevalence of burnout syndrome during the second semester of internship. Students who practiced their internship in a public hospital showed higher scores in emotional exhaustion and depersonalization than those who practiced in a private hospital.